Symphonic Poem “Rattanakosin Period (R.E.146-237)” - Potavanich, Vanich (Rangsit Music Journal, 2021)
Symphonic poem “Rattanakosin (R.E.146-237),” is a composition that uses melodic motives from various songs that play a role in Thai society as an element including King Rama IX’s Candlelight Blue, the Thai national anthem, Thai Royal Water Music (“Hae ruea”), and Ajarn Vijit Jitrangsan’s Rattanakosin (R.E.1-145) which describe Rattanakosin in the period R.E.1-145. The researcher intends to compose the songs to tell stories and events from the reign of King Rama IX to King Rama X by using elements from the musical composition of His Majesty King Bhumibol Adulyadej And the script of Rattanakosin by Ajarn Vichit Jitrungsan to connect events that occurred during R.E.146 until R.E.237 (B.E.2470-2561), focusing on the story during the reign His Majesty King Bhumibol Adulyadej.